Acne Vulgaris and Intake of Selected Dietary Nutrients—A Summary of Information - Podgórska, Aleksandra (Healthcare (Basel), 2021)
Acne vulgaris (AV) is a chronic disease that affects a significant percentage of the world’s population. Its development is influenced by both external and internal factors. The purpose of this review is to demonstrate the effect of basic nutrient intake on the exacerbation or alleviation of AV lesions. A retrospective review of publications in PubMed regarding diet therapy and the impact of individual nutrient intake on the skin condition of patients was conducted. Ingestion of products with a high glycaemic index may indirectly lead to sebum overproduction, which promotes infection with Cutibacterium acnes and causes inflammation. Consumption of certain dairy products may result in skin deterioration caused by the presence of hormones in these products, i.e., progesterone and testosterone precursors. The beneficial effect of fatty acids on the skin is manifested by the reduction in inflammation. Of significance in AV treatment are vitamins A, C, D, E and B, as well as mineral elements zinc and selenium. Proper nutrition may not only prevent or alleviate AV but also increase treatment efficacy.